Human Capital Convergence : International Evidence - Sab, Randa; Smith, Stephen (Washington, D.C. : International Monetary Fund, 2001)
In the growth literature, evidence on income convergence is mixed. In the development literature, health and education indicators are also often used. This study examines whether health and education levels are converging across countries and calculates their convergence speed, using data from 100 countries during 1970-96. A 3SLS procedure is used in a joint analysis of human capital convergence. The results confirm that investments in education and health are closely linked. We find unconditional convergence for life expectancy and infant survival, and enrollment rates, on average and by gender; and conditional convergence for all human capital indicators, including class size.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet